Implementasi Digitalisasi UMKM Produk Kopi dari Jagung: Sinergi Dosen dan Mahasiswa Dalam Program Kuliah Kerja Nyata - Indrajaya Indrajaya; M Muhamad Azan Pajri; Sakha Maulana Zikran; Aditya Haryanto Pratama; Arika Zahiro; Irvansah Roni; Orin Allysia; Putriatama Nilamsari; Nadya Bekasari; Afdiansyah Afdiansyah; Kristoper Kristoper; Sakti Satria; Nurshadrina Amalia Putri; Raihana Putri Nabilla (Lembaga Pengembangan Kinerja Dosen, 2026)
Digitalization is an effort to utilize digital-based technology to transform previously conventional work systems into more efficient and effective ones, including in the management of micro, small, and medium enterprises (MSMEs). This study aims to apply digitalization to corn-based coffe MSMEs in Talang Balai Baru 1 Village, Tanjung Raja District, Ogan Ilir Regency. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research findings indicate that the production and marketing activities of corn coffe MSMEs still use conventional methods. The implementation of digitaization has not been optimally implemented due to the low digital literacy of business owners and limited time in business managemen. Nevertheless, the initial implementation of digitalization through the use of social media and online sales platforms has had a positive impact in the form of expanding market reach and increasing ease of communication between producers and consumers. Thus, the digitalization of corn coffe MSME products has great potential to increase competitiveness and business sustainability if implemented gradually and continuously. .